Parental Uveitis Influences Offspring With an Increased Susceptibility to the Experimental Autoimmune Uveitis - Yin, Guangnian; Zeng, Wenxin; Hu, Kaijiao; Gao, Jie; Liu, Jianping; Chen, Yan; Chen, Feilan (Frontiers in Immunology, 2020)
Purpose: Previous studies have shown that parental abnormal physiological conditions such as inflammation, stress, and obesity can be transferred to offspring. The purpose of this study was to investigate the impact of parental uveitis on the development and susceptibility to experimental autoimmune uveitis (EAU) in offspring. Methods: Parental male and female B10RIII mice were immunized with interphotoreceptor retinoid binding protein (IRBP) 161-180 in complete Freund’s adjuvant and were immediately allowed to mate. Gross examination of the offspring gestated with EAU was performed to determine the influence of parental uveitis on offspring development after birth. Gene expression profiles were analyzed in the affected eyes of offspring under EAU to identify differentially expressed genes (DEGs). Adult offspring were given 5 μg, 25 μg, and 50 μg IRBP161-180 to compare their susceptibility to EAU. Immunized mice were clinically and pathologically evaluated for the development of EAU. Ag-specific T-cell proliferation and IL-17 production from spleens and lymph nodes were evaluated on day 14 or 35 after immunization. Results: Hair loss, delay of eye opening, and swollen spleens in the offspring from parents with uveitis were observed from day 14 to day 34 after birth. DEGs were involved in the immune system process, muscle system process, and cell development. The altered antigen processing and presentation, cell adhesion molecules, and phagosome in the eyes of the offspring from uveitis-affected parents were enriched. Offspring gestated with EAU showed a susceptibility to EAU and an earlier onset and higher severity of EAU compared to the control group mice. IRBP-specific lymphocyte proliferation and IL-17 production were observed in the EAU offspring with exposure to parental uveitis. Conclusions: The results suggest that mouse parents with uveitis can increase their offspring’s susceptibility to EAU, probably through altering cell adhesion molecules and antigen processing and presentation related to the T-cell proliferation and Th17 response.